Teachers’ Perceptions about Student Management in State Junior High School, Palembang City - Meilia Rosani; Valianti, Reva Maria; Lestari, Neta Dian (Graduate Program Magister Manajemen Pendidikan, 2023)
The purpose of this study was to examine how teachers at SMP Kota Palembang view student management in terms of admitting new students, documenting student data, grouping students, and coaching students. Obtained 150 samples from a population of 300 teachers or 50%. The research tool is a questionnaire using a likert scale which has been proven valid and reliable. The average score (mean) is used for data analysis. Based on research findings, state junior high school students are well managed, the results of the overall research implementation of student management in Palembang City Public Middle School. This is marked by an overall average score of 76% in the good category.